Analisis Konsentrasi Karbon Monoksida (CO) di Kota Makassar Periode 2019 – 2023 - Asdar, Meisya Putri Indrayani; Sri Suryani (JFT: Jurnal Fisika dan Terapannya, 2025)
Carbon monoxide (CO) is a hazardous gas produced by motor vehicles and industrial activities, with increasing concentrations in the air. Makassar, as a center of economy and urbanization, faces major challenges related to air quality. Efforts to reduce CO emissions are important to improve air quality and public health in Makassar City. The purpose of this study was to identify fluctuations in CO concentration trends in Makassar City during the period 2019 to 2023, to determine whether there was an increase, decrease, or a certain pattern and to see the factors that influenced it. The results showed that the CO concentration analyzed based on annual data showed a significant increase in CO emissions related to transportation, industrial, and urbanization activities. The analysis showed that urbanization, the number of motor vehicles, and weather patterns affected changes in CO levels. The CO concentration in Makassar showed an annual fluctuation of 1072.88%, which is considered very high, especially due to the large spike in CO concentration in 2022.